Análisis de la devolución de tributos internos por SUNAT según actividad económica manufactura, periodo 2018 - 2020 - García Martinez, Jhonattan (2021)
The return of internal taxes is a benefit that assist taxpayers for the balances in favor they obtain in the generation of their operational activities and in the legal framework of compliance with their tax obligations towards the Treasury, that is, to SUNAT. The present investigation called "Analysis of the Refund of Internal Taxes by SUNAT according to Manufacturing economic activity, period 2018 – 2020”, has the general objective of determining the evolution of the returns of internal taxes by SUNAT in the Manufacturing economic activity in the period 2018 to 2020. Likewise, the research was of a quantitative type and of a descriptive, non-experimental - transversal design. From the analysis and discussion of the results obtained, it was determined that the returns show an evolution with a negative trend for the study period.